California Packing Corporation. - Gordon, John C. (photographer):::Creator::::::::::::
The California Packing Corporation, or Calpak as it was commonly known, was founded in 1916 by the merger of five major canning enterprises - the California Fruit Canners Association, Griffin & Skelley, Central California Canneries, the J.K. Armsby Company and the Alaska Packers Association. This merger consolidated control not only of canning, drying and packing houses, but also of the brokers who sold these products and the farmers who grew them. http://www.historysanjose.org/cannerylife/through-the-years/1917-1966/cal-pak/index.html